Monosodium Glutamate Effects on Inflammation Status in Male Rats: Molecular and Physiological Study - Eman H. Al-Fadhili (Journal of Global Pharma Technology, 2016)
The current study included the effect of Monosodium Glutamate (MSG) on male rats by measuring the level of Physiological parameter by determining the level of total serum protein, albumin and by measuring the level of Molecular parameter by determining the level of IL-6, NF-κb, IKK and TNF-a. The study was conducted at in the Department of Biology, College of Science, University of Wasit from November, 2017 until April, 2018. Study was used nigh teen adult wister rats male weighing 150-250 g and 10-14 weeks age were used and then randomly divided into three group six animal in each group. The first group was control; while the second group was orally dose the MSG 100g/kg dissolved in distilled water and third group take orally dose from MSG 200g/kg dissolved in distilled water via orogastric gavages for 30 days. The results were as follows: weight gain significant increase (p ≤ 0.05) of for group that treatment with 100 mg/kg and 200 mg/kg when compare with control group and no a significant (p ≤ 0.05) in concentration of total serum protein, albumin and globulin in male rat that treated with MSG 100 mg /kg . Whereas serum total protein, albumin and globulin show a significant decreases in rats that treated with 200 mg /kg of MSG compere with control group, increases of Nf- κB treated with MSG as 100 mg/kg and 200 mg /kg when compere with control group, increases of IL-6 treated with MSG as 100 mg/kg and 200 mg /kg when compere with control group, increases of TNF-a treated with MSG as 100 mg/kg and 200 mg/ kg when compere with control group and decreases of IKK treated with MSG as 100 mg/kg and 200 mg/kg when compere with control group. Conclusion: MSG as food additive can cause weight increase, soluble total protein decrease significant, MSG increases gene expressionKeywords: MSG, Gene expression, Obesity